Acceptability of daily pre-exposure prophylaxis among adolescent men who have sex with men, travestis and transgender women in Brazil: A qualitative study. - Eliana Miura Zucchi; Marcia Thereza Couto; Marcelo Castellanos; Érica Dumont-Pena; Dulce Ferraz; Thiago Félix Pinheiro; Alexandre Grangeiro; Luís Augusto Vasconcelos da Silva; Inês Dourado; Leo Pedrana; Fernanda Soares de Resende Santos; Laio Magno (PLoS ONE)
Background Adolescents face socio-structural, personal and programmatic barriers to HIV prevention services, highlighting the importance of understanding knowledge and acceptability as essential aspects to promote their broader access to pre-exposure prophylaxis (PrEP). We analyzed the acceptability of PrEP among adolescent men who have sex with men (MSM), travestis and transgender women (TGW). Methods A qualitative investigation was conducted as part of the formative research of the PrEP15-19 study, an ongoing demonstration study that analyzes the effectiveness of daily PrEP among adolescent MSM, travestis and TGW aged 15-19 in three Brazilian cities. A total of 37 semi-structured interviews and 6 focus groups were conducted. Building from thematic analysis focusing on participants' sexual encounters, perceptions about PrEP efficacy, and vulnerability contexts, we analyzed prospective acceptability of PrEP. Findings Knowledge about PrEP was incipient and characterized by adolescents' frequent doubts about its prescription and efficacy. The 'ideal' use of PrEP appeared together with consistent condom use, especially in casual sex. PrEP use was also mentioned as depending on increased learning about prevention management over time. Main barriers to PrEP use included the incorporation of a daily medication into participants' routine and its impact on their social lives, especially related to stigma. Concerns over short- and long-term side effects were also reported as barriers to PrEP use. TGW and travestis contrasted using PrEP with the precarity of their life conditions, and some expressed a critical vision about PrEP by associating it with pharmaceuticalization and trans necropolitics. Conclusions Participants' low knowledge and acceptability of PrEP are circumscribed by a rigid perception of condom as the ideal prevention method and the context of their sexual relations. Prospective acceptability highlights that the successful uptake of PrEP depends on overcoming barriers of access to health services and confronting transphobia and homophobia as part of care.